Methods of Mushroom Substrate Waste Management by Young Mushroom Agropreneurs - Rosmiza Mohd Zainol; Mohd Nazri Mohd Tamami; Rosniza Aznie Che Rose; Jabil Mapjabil; Mazdi Marzuki (Penerbit Universiti Pendidikan Sultan Idris, 2018)
The mushroom industry is an environmentally friendly agricultural industry. This industry optimises the use of byproducts from other farms as the substrate for mushroom cultivation. Upon the harvest of mushrooms, musroom substrate waste has a high potential in the development of downstream industries. Nevertheless, non-environmentally friendly management of mushroom substrate waste has brought down the quality of the farming environment. The study was carried out to investigate the mushroom substrate waste management methods that are practised by agropreneurs and to assess their knowledge of environmentally friendly management of mushroom substrate waste. Qualitative (interview) and quantitative (survey) methods were carried out involving 40 agropreneurs who participated in the Kursus Pakej Projek Agropreneur Muda Cendawan which was organised by the Malaysian Department of Agriculture. The results show that most agropreneurs adopt non- environmentally friendly mushroom substrate management waste methods, namely by burning the mushroom substrate waste openly and collecting or discarding the waste to other places. However, the agropreneurs exhibit a high knowledge of caring for the environment towards mushroom substrate waste management. Their choice of waste management method depends on weather, the condition of the substrate (afflicted by disease and pests), as well as the agropreneurs’ attitudes. Therefore, environmentally friendly farm management approaches must be instilled in agropreneurs to ensure the sustainability of farming environments, increase in production, revenue generation for the agropreneurs, and the overall sustainability of the mushroom industry.